Bioabsorbable vascular scaffolds in routine practice: long-term results. (14th October 2021) - Mori, R M; Nunez, I N G
Abstract: Background: Recent publications suggest that bioabsorbable vascular scaffolds (BVS) carry an excess of thrombotic complications. Our goal was to describe the results in real life and in the long term, in a series of patients who received a BVS which is currently off the market. Methods: Two hundred and thirteen consecutive patients who received at least 1 BVS between May 2012 and December 2016 were analyzed. The primary objective was the incidence of the compound event "target vessel failure" that included infarction or target vessel revascularization and cardiac death. Results: Seventy-five percent of patients were men with a mean age of 61.4 years. They had a high prevalence of dyslipidemia (62.44%) and smoking (65.26%). The most common cause of admission was myocardial infarction without ST elevation (53.52%). A total of 233 coronary lesions were treated, with an average of 1.3±0.3 lesions per patient. The implant was successful in 99.5% of cases. Predilatation was performed in 89.3% and post dilation in 33.5% of cases. The use of intracoronary imaging (Optical Coherence Tomography OCT and/or Intravascular ultrasonography IVUS) to optimize the BVS implant was performed in 86 patients (40.38%). With a mean follow-up of 42.5 months, the incidence of target vessel failure was 6.57% during the first 24 months and 7.98% at the end of the follow-up. Regarding the device, this included 6 cases (2.81%) of thrombosis (definitive, probable or possible) and 10 cases (4.69%) of restenosis. Patients with a history of diabetes mellitus (HR 1.72 95% CI 1.01–2.95 P=0, 05) and/or chronic oral anticoagulation (HR 5.71 95% CI 1.12–28.94 P=0.04) had a higher risk of target vessel failure. The use of intracoronary imaging (OCT and/or IVUS) during the BVS implantation had a considerable trend toward significance as a protective factor (HR 0.32 95% CI 0.11–1.03 P=0.06). Conclusions: In this series of patients; in real life conditions, the incidence of target vessel failure was comparable to that previously described in randomized clinical trials. The events were more frequent during the first 2 years of follow-up, in the presence of greater cardiovascular comorbidity and in the absence of intracoronary imaging during the implantation. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): European Society of Cardiology